**Answer:**

Line d : y = -3x - 3

Line e : y = -3x - 2

Line f : y= -3x + 2

**Step-by-step explanation:**

Given that,

The slope of each line is -3.

Now,

We know that,

Equation of line is represented by y = mx + c

where m is the slope and c is the y-intercept.

Now,

Given that,

Line d goes through (0, - 3) and (- 1, 0).

So,

y-intercept of Line d is -3

∴ we get

**Equation of Line d is : y = -3x -3**

Now,

Given that,

Line e goes through (-1, 2) and (0, -2).

So,

y-intercept of Line e is -2

∴ we get

**Equation of Line e is : y = -3x - 2**

Now,

Given that,

Line f goes through (0, 2) and (1, -1).

So,

y-intercept of Line e is 2

∴ we get

**Equation of Line f is : y = -3x + 2**